Studi Model Interaksi Pengelolaan Program KB Lini Lapangan - Menara Simanjuntak; Lim Sanny (Bina Nusantara University, 2013)
Interaction model of family planning program management field lines are enhanced as one objective of family planning program revitalization. This research was conducted by exploration activities with qualitative approach (in-depth interviews and group discussion forums) for reconstructing a